Problems of horticultural activity in proximity to the city of Córdoba, Argentina: To the agroecological transformation - Ruggia, Ornela Paz (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2025)
The Horticultural Activity in Proximity to the City of Córdoba (HAPCC) refers to the production of fresh food that occurs in areas surrounding large marketing centers. During the last 30 years, the productive units that comprise it have suffered a process of reduction and intra-regional migration to locations far from the marketing centers. The objective of this work was to analyze the problems of the AHPCC, with the purpose of understanding what were the factors that led to this situation. The starting point is a qualitative methodology, through which 27 interviews based on a script were carried out with five groups of social actors recognized in the territory. The identified problems were grouped into five themes: territorial planning, access to land, calculation of costs and profits of products, inadequate regulations and precarious living and working conditions. The productive profiles affected by each identified problem were differentiated. It concludes about the need for a State that exercises its protectionist role to guarantee the rights of access to land of those who produce local fresh food. At the same time, emphasis is placed on the need to improve the working conditions of producers and a generational change that guarantees the continuity of the activity. Evidencing the urgent need to strengthen the HAPCC in particular and to transform the agri-food system from an agroecological perspective.